Verhalten ausgewählter Aminosäuren während eines Dreifachlangtriathlons - Volk, O.; Neumann, J. (Deutsche Zeitschrift für Sportmedizin, 2001)
We analyzed plasma amino acids and metabolic parameters in 9 triathletes before, during and after an ultratriathlon (11.4 km swimming, 540 km cycling, 126.6 km running). The average competition time was 48 h. The exercise led to a significant decrease in hematocrit from 48 ± 4 % to 45 ± 3 %. The concentration of the summed plasma amino acids (AA) decreased from 2590 ± 294 µmol/L to 2186 ± 409 µmol/L. The branched-chain amino acids (BCAA) decreased significantly from 449 ± 103 µmol/L to 355 ± 101 µmol/L. The aromatic AA (AAA) increased from 173 ± 34 µmol/L to 206 ± 38 µmol/L. The BCAA/AAA ratio decreased from 2.6 ± 0.5 to 1.7 ± 0.4. Pro, Orn, Gly, Ile, Val and Ala increased by 25-50 %. Tau, Phe and Tyr decreased by 20-30 %. Gln, Cys and Arg remained unchanged. In spite of continuous food intake, the exercise led to a significant decrease of glucogenic AA. The 48 h lasting triathlon resulted in a protein-catabolic state (serum urea increased from 7.0 ± 1.4 mmol/L to 9.2 ± 3.4 mmol/L, p<0.05) in spite of a slow moving speed.